How English Language Learning Textbooks Develop Learners’ Communication Skills, Creative Language Production, Critical Thinking and Collaborative Learning (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of this research is to explain how English language learning textbook can develop the language learners’ communication skills, creative language production, critical thinking and collaborative learning. Each skill is first explained in terms of definition and the targeted educational output sought. Then, the approaches to syllabus design that focus on developing these four skills are reviewed. Within each section of this research, the researcher sheds light on the teaching techniques involved. The researcher hopes to provide answers to the following questions: - What is the theoretical / psychological foundation of each skill? - What are the targeted educational outputs behind developing each skill? - How can these four skills be integrated in English textbooks? - What are the best classroom drills and teaching techniques required? - How can the assessment procedures help measure the learners’ progress in these skills? The findings of this research may be useful to those who are in charge of editing English textbooks and to the teachers of English as well.